Radiolarian tests as microhabitats for novel benthic foraminifera: Observations from the abyssal eastern equatorial Pacific (Clarion–Clipperton Fracture Zone). (September 2015) - Goineau, Aurélie; Gooday, Andrew J.
Abstract: We investigated benthic foraminifera inhabiting the empty tests of radiolarians in surface sediment samples from the abyssal Clarion–Clipperton Fracture Zone (13°50′N, 116°35′W; ~4080 m water depth), eastern equatorial Pacific, an area licensed for the future mining of polymetallic nodules. Based on two megacore samples (>150 µm, 0–1 cm sediment layer; 78.6 cm 2 surface area), we examined 288 radiolarian tests that were occupied by 'live' (Rose Bengal stained) inhabitants presumed to be foraminifera based on test morphology and wall structure; these quantitative data were supplemented by qualitative records from three additional cores. The radiolarian inhabitants comprised organic-walled and agglutinated monothalamous (single-chambered) and less common polythalamous (multichambered) forms. Among the 27 distinctive morphotypes, a few can be assigned to a described superfamily (Komokiacea) or to genera such as Lagenammina, Thurammina and Hormosinella, while two brown, organic-walled multichambered forms resemble the genera Hospitella and Placopsilinella . The remainder were assigned to informal morphotypes. The radiolarian inhabitants are generally small (<150 µm) and confined within the host test, although some construct delicate tubes, either flexible or rigid, on the exterior. Our study suggests that radiolarian tests represent an important small-scale (<500 µm) microhabitat for certain abyssal benthic foraminifera, possibly providing concentrations of food (e.g., bacteria) as well as protection. In many cases, the occupancy of radiolarian tests seems to be habitual rather than opportunistic. Thus, 19 of the 27 morphospecies, representing ~31% of total number of radiolarian inhabitants, were not observed outside this microhabitat. These habitual inhabitants represented ~8% of the total number of foraminiferal morphospecies in the samples and >9% of the total 'live' (stained) foraminiferal assemblage, thereby making a non-negligible contribution to local species diversity and foraminiferal abundance in our study area. Our new observations, and previous studies of benthic foraminifera inhabiting the empty shells of other foraminifera, suggest that high biodiversity among meiofaunal-sized deep-sea organisms (particularly foraminifera) is enhanced by the colonisation of small cryptic microhabitats. Based on their complex test morphology, we suggest that at least some of the diverse monothalamous foraminifera that typically dominate abyssal foraminiferal assemblages have little or no mobility, making them well suited to this mode of life. Highlights: We investigated live benthic foraminifera from the abyssal eastern equatorial Pacific. Foraminifera, including novel morphotypes, commonly inhabit empty radiolarian tests. We recognised 27 inhabiting morphospecies, 19 confined to radiolarian tests. The majority of the inhabiting forms represent undescribed species. Cryptic microhabitats may help to sustain local foraminiferal diversity.